Filming the Motherland: Gendered Violence and Pakistani Female Empowerment in Dukhtar and My Pure Land - Zainabb Hull (Janeway JS, 2020)
The revival of Pakistani cinema in the mid-2000s has heralded several successful films tackling relevant social issues, such as national identity, terrorism, and gendered violence. Pakistani filmmakers both at home and in the diaspora are using cinema to address women's rights issues within Pakistani communities worldwide whilst challenging simplistic and imperialist western perceptions of Pakistan and its people. This article analyses two recent female-led films from diasporic filmmakers: Afia Nathaniel’s Dukhtar (2014) and Sarmad Masud’s My Pure Land (2017). Each film features female leads navigating gendered violence, patriarchal oppression, and Pakistani cultural identity to explore the filmmakers’ own complicated relationships with the ‘motherland’, expressing a sense of belonging and nostalgic affection for Pakistan whilst holding the nation accountable for upholding patriarchal cultural values, in order to reveal paths towards gender equality and female empowerment in global Pakistani communities. Positive critical reception within Pakistan highlights both the difficulties faced by filmmakers addressing women's rights issues and the desire for Pakistani social dramas, indicating new possibilities within the media landscape. There remains a lack of insight into audience reception to new films addressing women's rights issues, and future research must examine how this new cinema might provoke and inspire positive social change within real world communities and for Pakistani women around the world. Nonetheless, in the production and global critical reception of Dukhtar and My Pure Land, there is evidence of Pakistan’s slow progress and growing enthusiasm for gender equality and safety, and of challenges to oppressive western perceptions of Pakistan that lead to paternalistic and racist treatment of South Asian women. These films prioritise the need for social change to come from within the community, offering up possible role models and futures for a Pakistan that is safe and fair for people of all genders.
Keywords: Romanticism; Gothic; poetry; Sexuality; Desire